Implementasi Marketing Mix dengan Pendekatan SWOT di UMKM Tradisional: Studi Kasus Gethuk Kethek Satu Rasa Salatiga - Ignatius Bias Galih Prasadhya; Ricky Arnold Nggili; Yoga Rizqi Prasmana; Big Greogory Kaitelapatay (Nur Science Institute, 2024)
Traditional culinary MSMEs, such as Gethuk Kethek Satu Rasa in Salatiga, play an important role in preserving Javanese culture and supporting the local economy, yet face challenges of competition and limited digital adoption. This study analyzes the application of the 7P marketing mix (Product, Price, Place, Promotion, People, Physical Evidence, Process) to enhance competitiveness and brand visibility. Using a descriptive qualitative approach, data were collected through semi-structured interviews with the owner and employees, supported by document analysis of the 2024 sales report and Instagram posts. The results highlight strengths in authentic cassava-based products (750 boxes/month), competitive pricing (IDR 16,000/box), strategic location attracting 60% of tourists, and customer satisfaction reaching 90%. Weaknesses include weak digital promotion (2–3 Instagram posts/month), fragile packaging, and manual production processes. SWOT analysis reveals opportunities from increasing tourist demand, digital training programs, and e-commerce collaboration, while threats stem from fast-food competition and a 15% rise in raw material prices since 2024. The study proposes strategies such as product diversification, digital marketing enhancement, entry into GoFood/Shopee, eco-friendly packaging, and adoption of packaging technology. These findings provide practical insights for traditional culinary MSMEs to integrate cultural heritage with digital innovation, offering relevance for both practitioners and academics.